Embedding Corporate Social Responsibility Into Corporate Strategy : A Review Of A Best Employer Company In Vietnam - Kim, Lin Siew (2010)
This thesis aims to understand and analyze th e incorporation of corporate social responsibility (CSR) into corporate strategy in a company in Vietnam that was recognized as one of the best employers in the country. Tesis ini bertujuan untuk memahami dan menganalisa penggabungan Tanggungjawab Sosial Korporat (CSR) ke dalam strategi korporat dalam sebuah syarikat di Vi etnam yang telah diiktiraf sebagai salah satu pengusaha terbaik di negeri tersebut